Safety and efficacy of a feed additive consisting of Bacillus velezensis NITE BP‐01844 (BA‐KING®) for chickens for fattening, chickens reared for laying, turkeys for fattening, turkeys reared for breeding and all avian species for fattening, or rearing to slaughter or point of lay including non‐food producing species (Toa Biopharma Co., Ltd.). (25th February 2022) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Fašmon Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of BA‐KING ® Bacillus velezensis when used as a feed additive for chickens for fattening, turkeys for fattening, chickens reared for laying, turkeys reared for breeding and all avian species for fattening, or rearing to slaughter or point of lay including non‐food producing species. The product under assessment is based on viable spores of a strain identified as B. velezensis, which is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the active agent was established, and it does not harbour acquired antimicrobial resistance genes, lacks toxigenic potential and does not have the capacity to produce aminoglycosides. Following the QPS approach to safety assessment, B. velezensis NITE BP‐01844 is presumed safe for the target species, consumers of products derived from animals fed the additive and the environment. Since no concerns are expected from the other components of the additive, BA‐KING ® is also considered safe for the target species, consumers of products derived from animals fed the additive and the environment. BA‐KING ® is not irritant to skin but is potentially irritant to eyes. In addition, should be considered a skin and respiratory sensitiser. The Panel is not in the position to conclude on the efficacy of BA‐KING ® for the target species.